Myoclonic epilepsy with photosensitivity in infants with Pallister-Killian Syndrome. (July 2019) - Ricci, Emilia; Bonfatti, Rocco; Rocca, Alessandro; Sperti, Giacomo; Cagnazzo, Valeria; Vignoli, Aglaia; Cocchi, Guido; Cordelli, Duccio Maria
Abstract: Introduction: Pallister-Killian Syndrome (PKS) (OMIM #601803 ) is a rare genetic disorder caused by a mosaic tetrasomy of the short arm of chromosome 12. Epilepsy is a frequent concern in PKS patients. Methods: we report 3 PKS patients, with early-onset myoclonic epilepsy and photosensitivity. In these children, we analysed epileptic history and the EEG phenotype. Results: Epilepsy onset was in the first 2 years of life in all patients and in 2 of them myoclonic seizures were the only seizure type. In all children photosensitivity was observed and myoclonic seizures were mainly related to low-frequency (1–6 Hz) intermittent photic stimulation. Levetiracetam was effective and well tolerated in the 2 treated patients. Conclusions: early-onset myoclonic epilepsy is a possible clinical manifestation of PKS. Low-frequency photosensitivity is a peculiar bioelectrical marker in these children. Highlights: We report 3 PKS patients, with early-onset myoclonic epilepsy and photosensitivity. Epilepsy onset was before the age of 2 in all patients and in 2 of them myoclonic seizures were the only seizure type. In all children myoclonic seizures were mainly related to low-frequency intermittent photic stimulation. The differential diagnosis between epileptic spasms and myoclonic seizures can be challenging in these patients. Levetiracetam was effective and well tolerated in the 2 treated patients.